THE MODELS OF CHECKLIST METHOD IN EVALUATING ELT TEXTBOOKS - Harni Jusuf (Al-Lisan: Jurnal Bahasa, 2018)
There are four interrelated aspects in teaching learning process that is teacher, students, materials, and evaluation and assessment. The things that should be paid attention related to materials are materials selection, materials development and design, and materials evaluation or textbook evaluation. Regarding to textbook evaluation, this article aims to describe one of the three methods of textbook evaluation, checklist method. It discusses what checklist method is and some suggested checklist method that can be used in evaluating textbook. There are eight different checklist models displayed in this article. They include Tucker (1975), Daoud and Celce-Murcia (1979), William (1983), Sheldon (1988), Cunningsworth (1995), Litz (2005), Mukundan and Nimehchisalem (2012), and Al Harbi (2017). The eight models are quoted from journals and books.